Strategic analysis of influx of foreign workers in Malaysia - Mohd Khamdani, Fatin Nadzira; Hairan, Muhammad Aiman Harith; Mustafa Kamal, Nur Mastura; Samsuden, Nurul Azira; Puteh, Fadilah (Faculty of Administrative Science and Policy Studies, 2025)
Foreign workers play a crucial role in filling labor gaps and supporting the workforce of this country for years. Nevertheless, uncontrolled foreign workers' influx can result in various challenges. This paper primarily focuses on the Malaysian Ministry of Human Resources (MoHR) effort to address the influx of foreign workers and its impact on the labor market. The study begins with external and internal analyses of the MoHR, utilizing the PEST analysis and a custom-made internal audit. Secondary sources and interviews with MoHR staff provide insights for the analysis. The SWOT matrix is used to present the findings and the TOWS Matrix guides the development of alternative recommendations. Through adoption of BOS, this paper proposes a set of strategic recommendations based on the strategic analyses using strategic management tools and techniques. These recommendations aim to address the challenges posed by foreign worker influx and improve the MoHR's management capabilities.